How to evaluate results from direct marketing campaigns involving targeting - Breur, Tom (Henry Stewart Talks, 2008)
Determining the (one-off) marketing and targeting effect, Tracking the (longitudinal) marketing and targeting effect over time, Evaluating costs and statistical power analysis, Best practice campaign selection process, The case for a reference group, The case for a random group, Why select in this order?, How to determine target depth, Wrap up